Green mobile devices and networks : energy optimization and scavenging techniques - Venkataraman, Hrishikesh; Muntean, Gabriel-Miro, 1972- (Boca Raton, Fla. : CRC Press, 2012)
"Powering the astounding functional advancement of mobile devices requires a revolution in the concept of battery life and recharge capability. This book provides insight into the principles and technical challenges behind automatically optimizing energy consumption in a dynamic real-time scenario. It discusses the continuous monitoring of battery life and the automatic adjustment of different functionalities including the reception mechanism, the complexity of the software modules, and the perceived video quality. It deals with different energy scavenging techniques and the technologies behind harvesting energy through sources like solar, light, acoustics, kinetic, mechanical vibrations, and electromagnetic waves"--
section 1. Optimization techniques -- section 2. Scavenging techniques.
"An Auerbach book."
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mobile communication systems -- Energy conservation; Green electronics; Electronic books